From Farmers to Firms: United States and China in a Shifting World Order: Dos Fazendeiros às Firmas: Estados Unidos e China numa Ordem Internacional em Transformação - Pereira da Silva Gama, Carlos Frederico; Furquim de Camargo, Fernando (Conjuntura internacional, 2018)
Ten years after the crisis, contradictions of a globalized capitalist economy rear their heads. The trade war between US and China provides surprising insights on its reorganization. China, an industrial powerhouse, claims respectability as an indispensable stakeholder in international regimes, as a challenged US retreats behind protectionism and punishing bilateralism.